Facilitating organizational ambidexterity through the complementary use of projects and programs. Issue 1 (January 2015) - Pellegrinelli, Sergio; Murray-Webster, Ruth; Turner, Neil
Abstract Creating and sustaining competitive advantage demands that firms both exploit knowledge and capabilities efficiently, and explore ways to innovate and respond flexibly. The study of this dual capability, ambidexterity, has become increasingly prevalent as organizations struggle to address rapidly changing environments. This paper draws upon longitudinal case research into a business transformation to study how organizational ambidexterity was achieved and sustained through the complementary use of programs and projects. In particular, a strategic, emergent approach to the management of the transformation program created flexibility, while the projects embedded in the program were managed to ensure the consistent, reliable and efficient delivery of new products, operating changes and key capabilities. In combining, but not conflating, these management approaches the organization responded successfully to discontinuous changes, and out-performed competitors. This paper adds to our knowledge of how ambidexterity works in practice and the use of projects and programs for implementing strategic change.